2010
DOI: 10.1177/1740774510367811
|View full text |Cite
|
Sign up to set email alerts
|

A tutorial on principal stratification-based sensitivity analysis: application to smoking cessation studies

Abstract: Background One problem with assessing effects of smoking cessation interventions on withdrawal symptoms is that symptoms are affected by whether participants abstain from smoking during trials. Those who enter a randomized trial but do not change smoking behavior might not experience withdrawal related symptoms. Purpose We present a tutorial of how one can use a principal stratification sensitivity analysis to account for abstinence in the estimation of smoking cessation intervention effects. The paper is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
48
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(48 citation statements)
references
References 41 publications
0
48
0
Order By: Relevance
“…11 In contrast, the structure-less approach of Rubin (1974) has spawned other definitions of direct effects, normally referred to as "principal-strata direct effect (PSDE)" (Frangakis and Rubin, 2002;Mealli and Rubin, 2003;Rubin, 2004Rubin, , 2005Egleston et al, 2010). Whereas the natural direct effect measures the average effect that would be transmitted in the population with all mediating paths (hypothetically) deactivated, the PSDE is defined as the effect transmitted in those units only for whom mediating paths happened to be deactivated in the study.…”
Section: Relation To Principal-strata Direct Effectmentioning
confidence: 99%
“…11 In contrast, the structure-less approach of Rubin (1974) has spawned other definitions of direct effects, normally referred to as "principal-strata direct effect (PSDE)" (Frangakis and Rubin, 2002;Mealli and Rubin, 2003;Rubin, 2004Rubin, , 2005Egleston et al, 2010). Whereas the natural direct effect measures the average effect that would be transmitted in the population with all mediating paths (hypothetically) deactivated, the PSDE is defined as the effect transmitted in those units only for whom mediating paths happened to be deactivated in the study.…”
Section: Relation To Principal-strata Direct Effectmentioning
confidence: 99%
“…A future research is to develop a simple method of sensitivity analysis for Assumptions 1 and 2. For the outcome with no censoring, simple methods have been proposed [17][18][19]. For the outcome with censoring, Shepherd et al [1] proposed a method, but the formulas shown in Appendix D are complex, and thus, it is difficult to implement this method.…”
Section: Discussionmentioning
confidence: 99%
“…For example, I recently used principal stratification in an investigation of the effect of a smoking cessation intervention on smoking withdrawal symptoms (Egleston et al, 2010). The intervention arm in the study received nicotine replacement therapy with a behavioral intervention.…”
mentioning
confidence: 99%
“…Subject matter experts have noted this problem and issued guidance recommending that smoking withdrawal symptoms only be investigated among those observed to abstain in a study (Shiffman et al, 2004). Since abstinence is a post-randomization variable, we can show that examining intervention effects within those stratified by observed abstinence status, as recommended (Shiffman et al, 2004), is flawed (Egleston et al, 2010;Pearl, 2009;Cole and Hernán, 2002;Imai et al, 2010).…”
mentioning
confidence: 99%